2014
DOI: 10.1177/0021998314545186
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties of carbon fiber/epoxy composites by incorporating XD-grade carbon nanotube

Abstract: Carbon fiber-reinforced epoxy composites (CFEC) were fabricated infusing 0–0.40 wt% XD-grade carbon nanotube (XD-CNT) using the compression molding process under 16 kips. XD-CNTs were infused into Epon 862 resin using a mechanical stirrer followed by a high intensity ultrasonic liquid processor. The mixture was then placed in a three-roll milling processor for three successive cycles at 140 rpm. Epikure W curing agent was added to the modified resin and mixed using a high-speed mechanical stirrer. Flexural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…The addition of 1 wt.% nanomaterials into epoxy resin is reasonable. Such uniform dispersion of nanomaterials created better interlocking performance between the fiber fabrics and matrix, which plays an important role in arresting the development of cracks in the epoxy matrix, and thus enhanced the load-carrying capacity of the CFRP composite during tensile loading [39,40]. Figure 8 shows a detailed comparison of the CFRP composites.…”
Section: Effect Of Various Nanomaterials On the Tensilementioning
confidence: 99%
“…The addition of 1 wt.% nanomaterials into epoxy resin is reasonable. Such uniform dispersion of nanomaterials created better interlocking performance between the fiber fabrics and matrix, which plays an important role in arresting the development of cracks in the epoxy matrix, and thus enhanced the load-carrying capacity of the CFRP composite during tensile loading [39,40]. Figure 8 shows a detailed comparison of the CFRP composites.…”
Section: Effect Of Various Nanomaterials On the Tensilementioning
confidence: 99%
“…From the results for absorbed energy on impact tests, it is observed that in general, the nanocomposites presented higher values of absorbed energy during the impact when compared to the pure PC/ABS matrix, which might F I G U R E 5 Dynamic-state rheological properties of the polycarbonate (PC)/poly(acrylonitrile-butadiene-styrene) (ABS) blend and the nanocomposites [Color figure can be viewed at wileyonlinelibrary.com] be explained by the appropriate transference of mechanical energy from the polymeric matrix to the CNTs; thus, the energy-absorbing capability increases, increasing the impact resistance. 33 As observed in Table 5, a significant increase of 26% and 36% on the impact resistance was achieved for MWCNTf -OC 1% and MWCNTf 2%, respectively, which can be explained by a strong electrostatic affinity between the reinforcements and the polymeric matrix 34 .…”
Section: Mechanical Propertiesmentioning
confidence: 73%
“…Hossain et al. 25 reported that with the addition of 0.3 wt.% of MWCNTs, flexural strength and modulus increased by 27% and 14%, respectively. Rahman et al.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Several studies have been conducted in relation to modifying the mechanical properties of fiber-reinforced polymer matrix composites through addition of CNTs. [23][24][25][26][27][28][29][30] Ulus et al 23 investigated the effect of MWCNTs addition on the flexural behavior of carbon fiber/ epoxy composites and the experimental results showed that flexural strength and bending stiffness with the addition of 0.3 wt.% of carbon nanotubes increased by 65% and 19.4%, respectively. Garg et al 24 investigated the effect of MWCNTs addition on the flexural behavior of glass fiber/epoxy composites and the obtained results showed that with the addition of 0.1 wt.% of carbon nanotubes, the flexural strength of glass fiber reinforced composites showed an improvement of 74%, as compared to the control sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation